Numerical Computation and Investigation of the Characteristics of Microscale Synthetic Jets. (2011) - Lee Lee, Ann Ann; Yeoh Yeoh, Guan H. Guan H.; Timchenko Timchenko, Victoria Victoria; Reizes Reizes, John John
Abstract : A synthetic jet results from periodic oscillations of a membrane in a cavity. Jet is formed when fluid is alternately sucked into and ejected from a small cavity by the motion of membrane bounding the cavity. A novel moving mesh algorithm to simulate the formation of jet is presented. The governing equations are transformed into the curvilinear coordinate system in which the grid velocities evaluated are then fed into the computation of the flow in the cavity domain thus allowing the conservation equations of mass and momentum to be solved within the stationary computational domain. Numerical solution generated using this moving mesh approach is compared with an experimental result measuring the instantaneous velocity fields obtained by μ PIV measurements in the vicinity of synthetic jet orifice 241  μ m in diameter issuing into confined geometry. Comparisons between experimental and numerical results on the streamwise component of velocity profiles at the orifice exit and along the centerline of the pulsating jet in microchannel as well as the location of vortex core indicate that there is good agreement, thereby demonstrating that the moving mesh algorithm developed is valid.